2017
DOI: 10.3989/scimar.04554.07a
|View full text |Cite
|
Sign up to set email alerts
|

Essential habitat for sardine juveniles in Iberian waters

Abstract: Summary:In a period when the Iberian sardine stock abundance is at its historical minimum, knowledge of the sardine juvenile's distribution is crucial for the development of fishery management strategies. Generalized additive models were used to relate juvenile sardine presence with geographical variables and spawning grounds (egg abundance) and to model juvenile abundance with the concurrent environmental conditions. Three core areas of juvenile distribution were identified: the Northern Portuguese shelf (cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Thus, being an area of high productivity (Fiúza, Macedo & Guerreiro, 1982;Fiúza, 1983), the north-west coast is suitable for small pelagic fish species and is therefore attractive to a large number of cetacean species (Zwolinski et al, 2010;Veiga-Malta et al, 2019). It is the area in Portuguese waters with the greatest abundance of sardine, the preferred prey of the common dolphin, and is the main nursery and recruitment area of this pelagic fish, centred off Aveiro-Figueira da Foz (40 -41 N) (Silva et al, 2009;Rodríguez-Climent et al, 2017). Massé et al (2018) reported an overlap between the sardine and the common dolphin in one of the core areas for sardine off central Portugal (39 -41 N).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, being an area of high productivity (Fiúza, Macedo & Guerreiro, 1982;Fiúza, 1983), the north-west coast is suitable for small pelagic fish species and is therefore attractive to a large number of cetacean species (Zwolinski et al, 2010;Veiga-Malta et al, 2019). It is the area in Portuguese waters with the greatest abundance of sardine, the preferred prey of the common dolphin, and is the main nursery and recruitment area of this pelagic fish, centred off Aveiro-Figueira da Foz (40 -41 N) (Silva et al, 2009;Rodríguez-Climent et al, 2017). Massé et al (2018) reported an overlap between the sardine and the common dolphin in one of the core areas for sardine off central Portugal (39 -41 N).…”
Section: Discussionmentioning
confidence: 99%
“…While summer shallow warm water habitat use around large estuary mouths such as the Guadalquivir, Tejo and the Gironde in the northeastern Atlantic has been associated with A. regius spawning [18,19,22], these estuaries are also important summer aggregation and spawning sites for small pelagic fishes. These include the European anchovy Engraulis encrasicolus [46] and the sardine Sardina pilchardus [47] both small pelagic fishes that can form an important part of adult A. regius's diet [48]. This suggests that A. regius may be exhibiting an income breeding strategy, advantageously spawning in areas of high prey abundance so that they have the required resources during gamete production and courtship.…”
Section: Plos Onementioning
confidence: 99%